OGICAL AND PETROGRAPHICAL PEСULIARITIES OF ROZANOVKA DYKE FIELD DOLERITES (INGUL MEGABLOCK OF THE UKRAINIAN SHIELD) - Mitrokhin, O.; Vishnevska, E. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The authors of this paper were the first to study Mafic dyke rocks drilled in deep boreholes in the southern part of the Ingul Megablock (IMB) of the Ukrainian Shield. The drilled dykes refer to the under-explored Rozanovka Dyke Field (RDF). The objective of the work was to determine the mineralogical and petrographical features of RDF dyke rocks which could further be used as an indicator to refer them, as well as other IMB mafic dykes, to certain regional magmatic associations. Under the authors’ tentative examination is the mineralogy of dyke rocks as well as the chemistry of the main rock-forming minerals: plagioclase, pyroxenes, and olivine. It has been established that among the studied samples there prevail cainotypic olivine dolerites showing mineralogical and petrographical features of the Proterozoic dolerite-diabase association. Being an indicator for the subplatform stage of ancient cratons development, the association is viewed as a paleoanalog of the continental plateau-basalt Phanerozoic association. Practical application of this finding is in identifying the potential Cu-Ni specialization of many well-known dolerite-diabase complexes. A more accurate definition of the petrography, geotectonic position and metallogenic specialization of RDF dolerites requires further geochemical research.